Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

CheetahBooks1

  • 3 years ago

5g + 4 (-5 + 3g) = 1 - g 5y+2 1/2 (10y + 4) 2(2k - 1) = 4(k-2) 4 - d = -(d - 4) 3d + 4 = 2 + 3d - 1/2 3(m + 1.5) = 1.5(2m + 3) 2y + 4x = 8; x= -2, 1, 3 4x = 3y - 7; x= 4,5,6 2y + 7x = 4; x= 5, 10, 15 6x = 7 - 4y; x= -2,-1, 0 ax - x = c y = x-v /b x/a = y/b 4(x-b)=x 2m - nx = x + 4 for x ax + 2xy = 14 for y A = (f+g/2) h for g

  • This Question is Closed

    Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy